Biological Parameter And Effect Of Abiotic Factors On The Developmental Stages Of Megaselia scalaris (Loew) (Diptera: Phoridae) - Teo, Bee Hsien (2014)
Biological parameters and the effect of different abiotic factors were tested on larval, pupal and adult stages of M. scalaris. For the biological parameters, comparison between males and females on the weight, size and lifespan of M. scalaris were examined. Parameter biologi dan kesan faktor- faktor abiotik yang berbeza telah dikaji terhadap peringkat larva, pupa dan dewasa M. scalaris. Bagi parameter biologi, perbandingan antara jantan dan betina terhadap berat, saiz, dan jangka hayat M. scalaris telah diperiksa.